Recent advances in the development of anode materials for solid oxide fuel cells utilizing liquid oxygenated hydrocarbon fuels: A mini review - Wang, Wei; Qu, J.; Julião, P.; Shao, Zongping (WILEY-V C H VERLAG GMBH, 2018)
© 2018 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim. Solid oxide fuel cells (SOFCs) are the most widely used fuel cells due to their excellent fuel flexibility, high efficiency and low emissions. Although the liquid fuels are easier to handle and transport than hydrogen, their direct use in SOFC leads to serious performance deterioration because of the coke formation on the traditional Ni-based cermet anodes. In this review, the advances in the development of coking resistant anodes and the new liquid fuels such as oxygenated hydrocarbons to solve the problem of coke formation with Ni-based anodes are summarized. It is concluded that Ni-based cermets are still the most promising anode materials and some targeted modifications are needed to improve the coking resistance. Several strategies to improve the coking resistance of Ni-based anodes are highlighted. The aim of this review is to provide some helpful guidance and potential directions for the future design of anodes for SOFCs utilizing liquid oxygenated hydrocarbon fuels directly.